Digital Reputation Management as a Low-Cost Innovation for MSME Economic Resilience: Evidence from Google Maps - Andini, Latifah Nirbita; Kurniawan, Angga (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the role of Google Business Profile management in building the digital reputation of the Dokter Xiaomi – Servicehpjogja.id MSMEs, with particular emphasis on business visibility, user engagement, and the influence of customer ratings and reviews. Methodology: This research employs a qualitative approach using a descriptive single-case study design. Data were collected from Google Business Profile performance reports during the observation period from September to December 2025, encompassing metrics such as impressions, traffic sources, user interactions, search queries, ratings, and customer reviews. The data were analyzed descriptively by aggregating and interpreting patterns in digital performance indicators. Results: The findings indicate that the business profile generated 11,524 views and 821 interactions, with 35.15% of the views originating from active searches, demonstrating alignment between profile information and user search intent. Furthermore, the Dokter Xiaomi – Servicehpjogja.id MSMEs achieved an average rating of 4.8 out of 5 based on 802 customer reviews, which function as a strong credibility signal and enhance consumer trust and preference. Applications/Originality/Value: The study confirms that integrating local search optimization with systematic customer review management is a low-cost yet effective digital marketing strategy that strengthens the reputation and competitiveness of service-based MSMEs. This research contributes to the digital marketing management literature by providing empirical insights from a micro enterprise context and offers practical guidance for MSMEs in developing sustainable digital reputation management strategies.